The effectiveness of development of creative problem-solving skills for tobacco control management of student leaders in a University - Chaiyasung, Phatcharaphan; Jornburom, Yodrawin; Sridet , Rutshaporn; Nanudorn, Anusorn (Thai Journal of Nursing, 2023)
This quasi-experimental research aims to examine the effectiveness of development of creative problem-solving skills for tobacco control management of student leaders in a university. A sample of 156 university students was purposively selected. The samples participated in the program to develop creative problem-solving skills in organizing tobacco control activities. The samples participated in the seven-week training program. The program activities included educational sessions and practical demonstration to build self-control and creative problem-solving skills related to tobacco control activities. Data were gathered using an online survey platform including the knowledge test on saying no to tobacco, skill assessment on creative problem-solving related to tobacco control activities, and satisfaction. Data were analyzed by descriptive statistics and paired t-test. The research results showed that after the program participation, the student leaders’ knowledge on saying no to tobacco and creative problem-solving skills were significantly higher than before the experiment (p < .001). Also, they were very satisfied with the program.